TANGGUNG JAWAB PEMERINTAH DAERAH TERHADAP FAKIR MISKIN DAN ANAK TERLANTAR PERSPEKTIF SIYASAH SYAR’IYYAH - MR, Resky Rahmadani; Anis, Muhammad (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2022)
Abandoned children and the poor are still social problems that require proper attention and treatment. The purpose of the study was to find out how the responsibility of the Bantaeng Regency Government is to handle the poor and abandoned children from the perspective of siyasah syar’iyyah. This research is a qualitative research with a juridical approach and syar’i theology. The results showed that the responsibility of the Social, Labor, and Transmigration Office of Bantaeng Regency in the care of the poor and abandoned children was carried out through mentoring, stimulant, education and financial assistance programs which began with accurate data collection. The program is quite effective despite obstacles, especially limited human resources and budget availability. Poverty alleviation and all social problems are closely related to the mission of Islamic teachings as rahmatan lil alamin, so that all efforts made by the government in principle are in accordance with the principles of benefit in the concept of siyasah syar’iyyah.